Le paysage urbain du centre ancien de Barcelone : outil d’analyse des processus de gentrification - Hovig Ter Minassian (Projets de Paysage)
The article questions the contributions and the limits of an analysis of the urban landscape, on the mode of the photographic itinerary, in the comprehension of the various forms of gentrification of the old center of Barcelona. The first part points out the landscape issues of the public rehabilitation policy which sought to revalorize the image of a district a long time considered as of bad reputation. The second part presents the methodology, which is based on a semiological reading of the landscape inspired by work of the geographer S. Rimbert and of the architect G. Chelkoff. The last part illustrates, with three examples, the contribution of the urban landscape analysis, following three axes : the logics of scales, the spatial inscription of the social transformations in the urban landscape and the role of the representations in the gentrification of a district.